PERANCANGAN ALAT PERAGA RCBO SEBAGAI PROTEKSI INSTALASI RUMAH TANGGA - Setiawan, Riko (Universitas Islam Balitar Blitar, 2025)
Non-standard electrical installations often cause fires due to short circuits. RCBO (Residual Current Circuit Breaker with Overcurrent Protection) is known to enhance electrical installation protection. People often neglect the dangers of non-standard electrical installations. This study designs a demonstration tool for an electrical protection system. The demonstration tool is intended to show that using non-standard electrical devices is hazardous. It effectively demonstrates the effectiveness of RCBO in protecting against abnormal conditions. The design includes testing MCB (Miniature Circuit Breaker) and RCBO as circuit breakers. The results show that RCBO is effective in minimizing electrical risks and plays a crucial role in protecting electrical equipment. In the short-circuit test, the RCBO tripped in 1.33 seconds, while the MCB tripped in 5.19 seconds. In the leakage current test, the RCBO was able to detect a leakage of 30 mA. Additionally, in the overload test at 1.8In, the RCBO tripped in 9.4 seconds, whereas the MCB tripped in 33.2 seconds. Thus, the RCBO demonstration tool created can visualize electrical hazard factors such as short circuits, leakage currents, and overloads. Moreover, the combination of RCBO and MCB is more effective as protection.